2007
DOI: 10.1007/s10310-006-0270-3
|View full text |Cite
|
Sign up to set email alerts
|

Root biomass and distribution of aPicea—Abiesstand and aLarix—Betulastand in pumiceous Entisols in Japan

Abstract: Root biomass and root distribution were studied in Entisols derived from the thick deposition of volcanic pumice on Hokkaido Island, Japan, to examine the effect of soil conditions on tree root development. The soil had a thin (<10 cm) A horizon and thick coarse pumiceous gravel layers with low levels of available nutrients and water. Two stands were studied: a Picea glehnii-Abies sachalinensis stand (PA stand) and a Larix kaempferi-Betula platyphylla var. japonica stand (LB stand). The allometric relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Such a proportion indicates that the organic soil layer with a depth of 0.13 m produced 72% of total CO 2 emitted to the atmosphere. The vertical distribution of CO 2 efflux can be explained by those of soil carbon content and root biomass, which were localized in surface soil (Sakai et al, 2007). The annual ecosystem respiration (RE) of this site was 1493 gC m −2 y −1 in 2003 (Hirata et al, 2007).…”
Section: Seasonal and Annul Sums Of Soil Co 2 Efflux (R S )mentioning
confidence: 90%
See 1 more Smart Citation
“…Such a proportion indicates that the organic soil layer with a depth of 0.13 m produced 72% of total CO 2 emitted to the atmosphere. The vertical distribution of CO 2 efflux can be explained by those of soil carbon content and root biomass, which were localized in surface soil (Sakai et al, 2007). The annual ecosystem respiration (RE) of this site was 1493 gC m −2 y −1 in 2003 (Hirata et al, 2007).…”
Section: Seasonal and Annul Sums Of Soil Co 2 Efflux (R S )mentioning
confidence: 90%
“…The soil is weakly acidic (pH 5.0-6.0) and poor in nutrients. Sakai et al (2007) reported that the densities of total and fine root biomass were 24.3 and 6.9 t ha −1 and more than 80% of root biomass was distributed in the topsoil with a thickness of 0.15 m. Total soil organic carbon (SOC) and nitrogen storage were about 36 tC ha −2 and 300 gN m −2 , respectively, and about 90% of SOC accumulated in the surface layer between 0-0.30 m (Sakai et al, 2007). 2 A·h) lead-acid battery that drives the system; Cmp = air compressor; P Air = compressed air from the air tank to the pneumatic cylinders for opening and closing the chamber lids; F 2 = air filter (0.5 mm mesh); S = sample air from the chamber; P = sample pump; W T = water trap; F 1 = air filter (1 µF mesh); IRGA = infrared gas analyzer; R = sampled air returned to the chamber.…”
Section: Soil Characteristicsmentioning
confidence: 99%
“…The A horizon and C horizon were stratified in order [34]; the B horizon was lacking. According to the record of Tomakomai Meteorological station (located 13 km south of the study site) for 1981-2010 [35], the annual mean air temperature was +7.6 • C, with monthly mean air temperatures of −3.8 • C (January) through +20.3 • C (August).…”
Section: Introductionmentioning
confidence: 99%
“…Soil was classified as a pumiceous volcanogenous regosol with high water permeability and poor nutrients [31,34], with 1-2 cm of a fresh litter layer and 5-10 cm of a decomposed organic layer (A horizon). The A horizon and C horizon were stratified in order [34]; the B horizon was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, root decomposition rates are affected by biotic factors, such as decomposer organisms present in the soil (King et al 1997, Silver & Miya 2001, Mao et al 2011, by abiotic factors, such as soil temperature, soil moisture and nitrogen availability; and by for-est management activities, such as fertilization and thinning (Silver & Miya 2001, King et al 2002. In addition, tree species can infl uence C and nitrogen (N) inputs from roots because the root litter produced by different species differs in quantity and quality of substrate (Sakai et al 2007, Mao et al 2011. Thus, the balance between roots and their decomposition controls the development of soil organic matter and the soil C and N content (Silver & Miya 2001).…”
Section: Introductionmentioning
confidence: 99%